-3(2-5x)=15x-6

Simple and best practice solution for -3(2-5x)=15x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2-5x)=15x-6 equation:


Simplifying
-3(2 + -5x) = 15x + -6
(2 * -3 + -5x * -3) = 15x + -6
(-6 + 15x) = 15x + -6

Reorder the terms:
-6 + 15x = -6 + 15x

Add '6' to each side of the equation.
-6 + 6 + 15x = -6 + 6 + 15x

Combine like terms: -6 + 6 = 0
0 + 15x = -6 + 6 + 15x
15x = -6 + 6 + 15x

Combine like terms: -6 + 6 = 0
15x = 0 + 15x
15x = 15x

Add '-15x' to each side of the equation.
15x + -15x = 15x + -15x

Combine like terms: 15x + -15x = 0
0 = 15x + -15x

Combine like terms: 15x + -15x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 11x-20=9x+11 | | -18x+12=2-19x | | 9x-1=3x+8 | | 6(x-1)=x-6 | | (2x-1)=121 | | 4(5)+5y=2 | | 2/5*220 | | 5(x+3)=2x+33 | | 4sin^2x= | | Dy/dx=cosx/2 | | V=cosx/2 | | -6x+12=-60 | | 7(3)+3x=-21 | | 4x+6=-18-2x | | 7y+3(-7)=-21 | | 12-4x=-9x-3 | | x/2-7/2=-5 | | x-3=9x+54 | | 3(x-1)+4(x-2)=12x+4 | | 5x-3(x-2)=0 | | 2+7x=-28+x | | -6+12=-60 | | x-3(x-1)=-9 | | 2x-4(x-3)=x-6 | | 9+10(2)=x | | 15x+7=-3x+25 | | x*y=21 | | Y-20+10=70 | | x^2=x*-1 | | 23x=x | | 20y+20=70 | | 20y+10=80 |

Equations solver categories